Kualitas Mie Basah dengan Substitusi Tepung Bonggol Pisang Kepok (Musa acuminata balbisiana C.) dan Umbi Bit (Beta vulgaris L.) - Liya Hertanti, Beatrik; Pranata, Franciscus Sinung; Reni Swasti, Yuliana (Jurnal Teknologi Pangan dan Hasil Pertanian, 2023)
Noodle is a popular food and mostly consumed by people in Indonesia. The addition of kepok banana corm and beetroot flour as potential local foodstuff is expected to increase nutritional content, especially fibre content in wet noodle product. This research aims to determine the effect of substitution of kepok banana corm and beetroot flour on the physical, chemical, microbiological, and organoleptic qualities of wet noodle, and to determine the best substitution ratio of kepok banana corm and beetroot flour to produce wet noodle with the best quality. This research used a completely randomised design with four treatments are control treatment (100:0:0), A (70:10:20), B (70:15:15), and C (70:20:10) with three repetitions. The results of this research are wet noodles have moisture content of 54,59-62,80%, ash content of 0,79-1,16%, protein content of 3,53-6,60%, insoluble fibre content of 7,81-9,50%, soluble fibre content of 4,84-10,82%, fat content of 2,43-6,48%, carbohydrate content of 25,99-35,56%, and water absorption of 37,38-43,86%. The results of microbiological analysis of wet noodles are ALT 0,43 x 102  to 11,73 x 102 () and AKK 0,08 x 102  to 0,26 x 102 (). The best quality of wet noodle is treatment C based on chemical, physical, microbiological, and organoleptic parameters